Nephrotoxicity of Calcineurin Inhibitors in Kidney Epithelial Cells is Independent of NFAT Signaling - Andrea Karolin; Andrea Karolin; Geneviève Escher; Stefan Rudloff; Daniel Sidler (Frontiers Media S.A., 2022)
Background: Calcineurin inhibitors (CNIs) such as cyclosporine A and tacrolimus are commonly used after renal transplantation to suppress the immune system. In lymphoid cells, cyclosporine A acts via the calcineurin/nuclear factor of activated T-cell (NFAT) axis. In non-lymphoid cells, such as kidney epithelial cells, cyclosporine A induces calcineurin inhibitor toxicity. It is unknown via which off-targets cyclosporine A induces calcineurin inhibitor toxicity in kidney epithelial cells.Methods: To measure a compound's potential to induce nephrotoxicity, the expression of the surrogate marker Fn14 was measured by flow cytometry. Compounds were tested for their potential to induce Fn14 either chemically or plasmid-mediated. Mice were injected with various compounds, and changes in nephrotoxic gene expression levels of the kidney epithelial cells were then analyzed.Results: Fn14 is specifically upregulated due to calcineurin inhibitor toxicity inducing agents. Inhibition of the NFAT axis showed no increase of the Fn14 expression on the surface of kidney cells. However, inhibition of p38 MAPK, phosphoinositide-3-kinase (PI3K)/Akt, protein kinase C (PKC), and inhibitor of nuclear factor-κB (IκB) kinase (IKK) showed clear induction of Fn14 and increased expressions of nephrotoxic, inflammatory, and fibrotic genes in vitro and in vivo.Conclusions: These findings show that cyclosporine A acts independently of NFAT on kidney epithelial cells. Moreover, inhibition of serine/threonine protein kinases mimics cyclosporine A's activity on kidney epithelial cells. This mimicking effect indicates that these protein kinases are off-targets of cyclosporine A and damage structural renal cells when inhibited and therefore contributes likely to the development and progression of calcineurin inhibitor toxicity.